2002
DOI: 10.1021/bi0117910
|View full text |Cite
|
Sign up to set email alerts
|

Obelin from the Bioluminescent Marine Hydroid Obelia geniculata:  Cloning, Expression, and Comparison of Some Properties with Those of Other Ca2+-Regulated Photoproteins

Abstract: A cDNA encoding the Ca2+-regulated photoprotein of the bioluminescent marine hydroid Obelia geniculata was cloned and sequenced. The cDNA is a 774 bp fragment containing two overlapping open reading frames, one of which contained 585 bp encoding a 195 amino acid polypeptide which obviously has the primary structure of the apoprotein of a calcium-regulated photoprotein. Many of the residues are identical to those in other Ca2+-regulated photoproteins: 86% compared with that from Obelia longissima, 76% with that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(134 citation statements)
references
References 41 publications
6
125
0
3
Order By: Relevance
“…This suggestion is also supported by the results of CcbP localization, which showed that it was present in vegetative cells but absent from heterocysts (Fig. 5) (30). Although the maximum fluorescence emission of recombinant obelin-Ca 2ϩ in vitro is at 517 nm (30), the peak of obelin-Ca 2ϩ fluorescence emission is at 460 nm in Anabaena cells (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…This suggestion is also supported by the results of CcbP localization, which showed that it was present in vegetative cells but absent from heterocysts (Fig. 5) (30). Although the maximum fluorescence emission of recombinant obelin-Ca 2ϩ in vitro is at 517 nm (30), the peak of obelin-Ca 2ϩ fluorescence emission is at 460 nm in Anabaena cells (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…For instance, in obelin (state II) the N 2 atoms of His-22 and His-24 (helix A) form hydrogen bonds with carbonyl oxygens of Trp-179 (helix H) and Gly-193 (C terminus); N 1 and N 2 atoms of Arg-21 (helix A) are hydrogen bonded with the carbonyl oxygen of Phe-178 (helix H), with the O␦ 1 oxygen of Asp-187 (C terminus), and with the oxygen of Pro-195, all situated in the C terminus. All these listed hydrogen bonds persist in the Ca 2ϩ -discharged obelin having bound coelenteramide and calcium (state III) and this strengthens the idea that the binding cavity remains inaccessible for solvent, thus providing the environment favoring the efficient fluorescence of the bound coelenteramide in the Ca 2ϩ -discharged photoproteins (8,24). Ca 2؉ -Binding Loops.…”
Section: Resultssupporting
confidence: 58%
“…The best studied proteins using this luciferin are the Ca 2ϩ -regulated photoproteins such as those responsible for the bioluminescence of marine coelenterates (1), for example, aequorin from the jellyfish Aequorea (2, 3) and obelin from the hydroid Obelia (4,5). All of the photoproteins characterized to date consist of a single polypeptide chain with high sequence homology and contain three ''EF-hand'' Ca 2ϩ -binding consensus sequences (6)(7)(8) like some other Ca 2ϩ -binding proteins (9). Their bioluminescence property derives from the fact that they contain in their active site an ''activated'' coelenterazine, 2-hydroperoxycoelenterazine, tightly but noncovalently bound.…”
mentioning
confidence: 99%
“…The fast kinetics of photoprotein luminescence provides a sensitive means of studying the early steps, which lead from calcium binding to activation of EF-hand-based calcium sensors. The structural homology among various photoproteins suggests that their [Ca 2ϩ ] depen-dence obeys the same rules, despite different maximum luminescence rates (22,23). Photoproteins contain a pseudo-EFhand motif, which does not bind Ca 2ϩ (6,13).…”
Section: Discussionmentioning
confidence: 99%